Tax pass-through in the European beer market - Aria Ardalan; Sebastian G. Kessing (Philipps-University Marburg, School of Business and Economics, 2017)
We study the pass-through of indirect taxes on beer prices in the European Union (EU). Exploiting the variation of value added tax rates, beer excise tax rates, and beer prices in a panel of monthly data from 1996 to 2016 of all current 28 EU member states, we estimate the tax pass-through of specific beer excise taxes and ad valorem value added taxes, respectively. Ad valorem taxes are under-shifted at a rate of approximately 70%. Specific excise taxes are almost fully shifted to prices in the EU, but, in contrast to the empirical findings for the US, there is no evidence of over-shifting. Nevertheless, the difference between ad valorem and specific tax pass-through rates indicates that imperfect competition plays an important role in the European beer market.
Keywords: H22; H23; 330; Tax incidence; Pass-through; VAT; Excise Taxes; EU